Fracture-vuggy carbonate reservoir characterization based on multiple geological information fusion - Wang, Yan; Xie, Pengfei; Zhang, Huitao; Liu, Yuming; Yang, Aiying (Frontiers in Earth Science, 2024)
In response to the complexity and strong heterogeneity of carbonate reservoirs with fracture-vuggy structures, we propose a multi-element information fusion modeling approach that incorporates the integration of multiple methods and multi-probability fusion at various facies and scales. First, the statistics between frequency of karst and geological information are acquired, and we quantify the statistics to regression equations. Second, these regression equations are transferred to probability bodies. The probability bodies can be applied in modeling as a soft control. But just one single body can be input in modeling process. Third, multiple probability bodies are fused into a fusion probability body by a probability fusion algorithm, which can keep the potential information of probability bodies. Finally, we apply the probability body in modeling workflow. By this way, the fusion method bridges the gap of geological information and modeling. The geological mechanism on karst makes the modeling method meet the real model better. The model established through the proposed method showcases a significant level of consistency with reservoir re-evaluation, achieving an impressive 90% degree of alignment.The result shows that the model established by the proposed method exhibits a high degree of consistency with reservoir re-evaluation and numerical simulation resultsthe history match shows a high correlation, serving as a dependable basis for making adjustment to development plans.